A Mild Laryngeal Cleft Causes Severe Symptoms. Issue 3 (March 2019) - Mandadi, Akhila Reddy; Saeed, Wajeeha; Suneja, Upma; Waseem, Muhammad
Abstract : Abstract: Diagnosis and treatment of laryngeal clefts (LCs) particularly type I pose a challenge. Although rare, type I LCs are becoming increasingly identified in recent years, and this is perhaps due to both an increased awareness and better diagnostic modalities. We report a young infant presenting with feeding difficulty and respiratory distress related to LC. The pertinent literature is also reviewed.